2019
DOI: 10.3390/ijerph16224469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics Supplementations on Health Status of Athletes

Abstract: Athletes are prone to several health complications, including upper respiratory tract infections, allergies, and gastrointestinal discomforts during practice and after the performance due to the intense exercise, travel, insufficient rest and restricted food consumption. Probiotics are well known as complementary therapeutic and health supplements for several diseases and disorders. Studies suggest that the intervention of probiotics improved the health status of elite athletes, but the results are not consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…There was a probiotic strain in combination with oral metronidazole that was not able to reduce BV recurrence [ 51 ]. The lack of success in clinical trials with probiotics as modulators of fertility disorders may be due to the efficacy of the probiotic being strain- and disease-dependent, as well as highly reliant on the dose, duration, administration method, and host state [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a probiotic strain in combination with oral metronidazole that was not able to reduce BV recurrence [ 51 ]. The lack of success in clinical trials with probiotics as modulators of fertility disorders may be due to the efficacy of the probiotic being strain- and disease-dependent, as well as highly reliant on the dose, duration, administration method, and host state [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…To find probable sources of between-study heterogeneity, subgroup analyses were conducted based on sex (Male/Female/Both genders), age (<40 year/>40 year), study design (Parallel/Cross-over), supplement dosage (=10 9 />10 9 CFU/day), duration of intervention (<3 /≥3 weeks) and probiotic type (Lactobacillus/Bifidobacter/Different types), using a fixed-effects model. The duration of 3 weeks and the dosage of 10 9 CFU/day were selected based on previous studies 21 , 22 . All statistical analyses were done using Stata software, version 11.2 (Stata Corp, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%
“…8 It could be suggested that the use of probiotics in physically active individuals might serve as a strategy to further improve respiratory symptoms and inflammatory status, and in consequence increase the physical performance of athletes. 8 Although a recently published review has indicated that probiotic supplementation improves the immune system and reduces the severity and incidence of upper respiratory tract infections in athletes 9 , to the best of our knowledge there has been no systematic literature review or meta-analysis that has confirmed these results.…”
Section: Introductionmentioning
confidence: 99%